Lymphatic filariasis control in Tanzania: effect of repeated mass drug administration with ivermectin and albendazole on infection and transmission. - Paul E Simonsen; Erling M Pedersen; Rwehumbiza T Rwegoshora; Mwelecele N Malecela; Yahya A Derua; Stephen M Magesa (Public Library of Science (PLoS), 2010)
In most countries of sub-Saharan Africa the control of lymphatic filariasis (LF) is based on annual mass drug administration (MDA) with a combination of ivermectin and albendazole, in order to interrupt transmission. Here we present the first detailed study on the effect of 3 repeated MDAs with this drug combination, as implemented by the Tanzanian National Lymphatic Filariasis Elimination Programme (NLFEP).Infection and transmission was monitored during a five-year period (one pre-intervention and four post-intervention years) in a highly endemic community (Kirare village) in north-eastern Tanzania. The vectors were Anopheles gambiae, An. funestus and Cx. quinquefasciatus. After start of intervention, human microfilaraemia initially decreased rapidly and statistically significant (prevalence by 21.2% and 40.4%, and mean intensity by 48.4% and 73.7%, compared to pre-treatment values after the first and second MDA, respectively), but thereafter the effect levelled off. The initial decrease in microfilaraemia led to significant decreases in vector infection and vector infectivity rates and thus to a considerable reduction in transmission (by 74.3% and 91.3% compared to pre-treatment level after first and second MDA, respectively). However, the decrease in infection and infectivity rates subsequently also levelled off, and low-level transmission was still noted after the third MDA. The MDAs had limited effect on circulating filarial antigens and antibody response to Bm14.Critical issues that may potentially explain the observed waning effect of the MDAs in the later study period include the long intervals between MDAs and a lower than optimal treatment coverage. The findings highlight the importance of ongoing surveillance for monitoring the progress of LF control programmes, and it calls for more research into the long-term effect of repeated ivermectin/albendazole MDAs (including the significance of treatment intervals and compliance), in order to optimize efforts to control LF in sub-Saharan Africa.